Factors Affecting the Selection of Accommodation Services in Mueang District, Songkhla Province - Nutsamai, Chutikran; masasa, Suhaida; Pohsa, Kuarueming; Bilraheem, Natcha; Tansoo, Phakpoom; Thongnueakhaeng, Jaruwan (Journal of Management Sciences, Songkhla Rajabhat University, 2024)
The purpose of this research was to study the behavior of tourists who influence the decision to choose accommodation in Songkhla Province and to study the combination of marketing that affects the decision to choose accommodation services in Songkhla Province by using a questionnaire as a tool to collect data from Thai tourists who come to use accommodation services. The results of the study are as follows: The results of the study are as follows: Thai tourists who come to use the accommodation service. In Mueang District, Songkhla Province, the level of expectation for choosing accommodation services in Mueang District, Songkhla Province is very high at an average of 3.80 and the S.D. value is 3.80 with a statistically significant implication at the level of 0.10. Thai tourists who come to use the accommodation service. In Mueang District, Songkhla Province, with different genders and incomes. There is a level of expectation of Thai tourists who come to use the accommodation service in Mueang District, Songkhla Province. However, considering the different ages, statuses, education levels, and occupations, there are expectations of Thai tourists who come to use the accommodation services in Mueang District, Songkhla Province